2016
DOI: 10.1111/jth.13337
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent venous thromboembolism after discontinuation of vitamin K antagonist treatment: a nested case–control study

Abstract: EssentialsVitamin K antagonists (VKA) in venous thromboembolism (VTE) lower the risk of recurrences. 41 841 VKA-treated VTE patients had 1242 recurrent VTEs on therapy or early after cessation. An increased risk of recurrence was found in the first 120 days after VKA cessation. Patient education for the early detection of recurrent VTE after VKA cessation is recommended.Summary. Background: The standard treatment for venous thromboembolism (VTE) and the prevention of recurrent VTE (rVTE) consists of anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…This is consistent with a previous observation from this trial demonstrating that the difference in D‐dimer levels between the treatment groups was driven by the absence of an increase in D‐dimer following rosuvastatin use . As both thrombin generation and D‐dimer are markers of hypercoagulability , the current results provide further evidence that rosuvastatin may prevent a rebound phenomenon; that is, a shift to a more procoagulant profile along with increased risk of a recurrence of VTE after the sudden withdrawal of anticoagulant treatment . Preventing such a rebound hypercoagulability may be a further benefit to patients with previous VTE in whom anticoagulation is withdrawn.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with a previous observation from this trial demonstrating that the difference in D‐dimer levels between the treatment groups was driven by the absence of an increase in D‐dimer following rosuvastatin use . As both thrombin generation and D‐dimer are markers of hypercoagulability , the current results provide further evidence that rosuvastatin may prevent a rebound phenomenon; that is, a shift to a more procoagulant profile along with increased risk of a recurrence of VTE after the sudden withdrawal of anticoagulant treatment . Preventing such a rebound hypercoagulability may be a further benefit to patients with previous VTE in whom anticoagulation is withdrawn.…”
Section: Discussionsupporting
confidence: 91%
“…11 After withdrawal of anticoagulant treatment, D-dimer levels normally increase, which is called the rebound phenomenon. 33,34 D-dimer levels are the result of the amount of available fibrin and the fibrinolytic potential. Rosuvastatin is expected to lower fibrin levels by reducing clotting factors and by its anti-inflammatory effects, and to increase the fibrinolytic potential.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blood sampling was done 3 months after discontinuation, which is fundamentally different from the original models (Vienna and DASH), where blood is drawn 1 month after discontinuation. This may have led to underestimation of risks, as some studies have suggested a rebound phenomenon in which several markers of coagulation, including D‐dimer levels, increase shortly after anticoagulant treatment is withheld and because the risk of recurrence is highest shortly after anticoagulation withdrawal . Of note, 52 patients had a recurrent event before D‐dimer testing and were not included in the analyses as this could lead to immortal time bias.…”
Section: Discussionmentioning
confidence: 99%